A Post-traumatic Defense Mechanism on Toni Morrison’s Portrayal of Pecola in The Bluest Eye - Farah, Farhat Tasannum (International Journal of Humanities and Education Development (IJHED), 2021)
Trauma is a universal experience of human being. The intensity and characteristics of traumatic experiences vary from person to person, culture to culture; and they also depend on the other psycho-socio-cultural variables; and the defense-mechanism has no particular order. In order to making points clearer and focused, this paper has been divided into three subsections. The first section is a narrative essay on trauma and post-traumatic ego defense mechanism. The second part broadly focuses on some common defense mechanism and the third section discusses on a particular defense mechanism, dissociating reality and associates it with the idea of insanity. As a whole, this research paper deals with Post-traumatic Defense Mechanism, focuses on the character of Pecola as a mother in The Bluest Eye by Toni Morrison that reads a deconstructed idea of “insanity” to interpret the character.